An Ethico-Phenomenology of Digital Art Practices - Torre, Giuseppe (London : Routledge, 2020)
Digital art practitioners work under the constant threat of a medium - the digital - that objectifies the self and depersonalises artistic identities. If digital technology is a pharmakon in that it can be either cure or poison, with regard to digital art practices the digital may have in fact worked as a placebo that has allowed us to push back the date in which the crisis between digital and art will be given serious thought. This book is hence concerned with an analysis of such a relationship and proposes their rethinking in terms of an ethico-phenomenological practice informed by an in-depth understanding of the digital medium. Giuseppe Torre engages with underground cultures such as Free and Libre Open Source Software (FLOSS) and its ties with art discourse. The discussion is informed by various philosophical discourses and media theories, with a focus on how such ideas connect back to the existing literature in performance studies. Replete with examples of artwork and practices, this book will be of great interest to students and scholars of theatre and performance studies, art and technology.
OCLC-licensed vendor bibliographic record.
Keywords: Computer art; Arts, Modern -- 21st century; PERFORMING ARTS / Theater / General; PERFORMING ARTS / General; TECHNOLOGY / General